Analisis Perlindungan Hukum Pada Anak Dalam Prespekstif Hak Terhadap Manusia - Faturohman Faturohman; Nana supriatna; Winda Putri Julianah (Jurnal Hukum dan Sosial Politik, 2024)
Legal protection for children is a very crucial aspect in efforts to ensure the fulfillment of human rights, especially for children. Children are immature people and must be protected as strictly as possible. The implementation of this legal protection still faces various challenges, including a lack of awareness among the public regarding their rights and also the existence of a culture that can sometimes conflict with the principles of human rights. This more integrated and sustainable effort from various parties, including the government and the general public, can protect a right that is carried out effectively. Education and public awareness regarding important things to protect children's rights, such as improving an environment that can develop and also the overall welfare of children.